Empowering Data-Driven Decision Making: A Review on Visual Analytics - Megha Narayanan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The power of analyzing large, complex, diverse, or dynamic data is associated with how effectively we can find the patterns or associations the data holds, and gain insights from it within time constraints. Visual analytics, termed as a blend of analytical reasoning and visualization, helps in increasing this effectiveness. In the modern era of technological revolution, the importance of finding rapid solutions to any problem is immense. With the complete reliance on data rather than intuitions, data-driven decision making improves efficiency, accuracy, scalability and reduces potential risks related to deriving effective solutions. One among the approaches of empowering data-driven decision making is Visual Analytics. This paper presents a detailed review on visual analytics. A proper definition of visual analytics is put forward, followed by reviewing the works done in the area for various fields. The state of the art and challenges are investigated and future scope of visual analytics is addressed. Furthermore, the paper explores basic visual analytics approach by conducting a case study on implementing a model to diagnose common cold and influenza in patients with suspected symptoms.